BANDUNG JENGKI FROM HERITAGE POINT OF VIEW: DOCUMENTATION AND PRELIMINARY SEARCH ON SIGNIFICANCE (DIMENSI: Journal of Architecture and Built Environment, 2016)
Jengki architecture is one of Indonesian post-colonial architecture style popular in 1950 to 1970. Most study of Jengki was done in Jakarta, Semarang, and Malang. In Bandung, there is no written record of Jengki identification or documentation found. This paper tries to recognize and document Jengki typology in Bandung as a preliminary study on its presences, and its variant, in the city. It also tries to look at this typology from heritage point of view, whether there is significance in accordance to heritage criteria. Using site survey and Google street view, data were collected and elaborated in table to recognize Jengki traits in a suspected building. Building’s significances were then reviewed using criteria mentioned in local legislation.  It is found that not all suspected Jengki building contain all Jengki traits rather more late modern Indonesian character.  Private buildings were assessed to have less heritage value, while public building retains more. Deeper study and documentation on Jengki in Bandung are still needed to legitimate Jengki as heritage since there is no study ever done previously on this issue